Recombination and ligation of transfected DNA in CHO mutant EM9, which has high levels of sister chromatid exchange. - Hoy, C A (1987)
Transformation frequencies were measured in CHO mutant EM9 after transfection with intact or modified plasmid pSV2-gpt. The mutant and wild-type strain behaved similarly under all conditions except when homologous recombination was required to produce an intact plasmid. Therefore, the defect of the mutant which renders it slow in DNA strand break rejoining and high in sister chromatid exchange induction reduces its ability to recombine foreign DNA molecules.